A‐kinase‐interacting protein 1 overexpression correlates with deteriorative tumor features and worse survival profiles, and promotes cell proliferation but represses apoptosis in non‐small‐cell lung cancer. Issue 2 (11th December 2019) - Chen, Hui; Yan, Shaohui; Dong, Lixin; Li, Xin
Abstract: Background: This study aimed to explore the correlation of A‐kinase‐interacting protein 1 (AKIP1) expression with clinical characteristics as well as survival profiles in non‐small‐cell lung cancer (NSCLC) patients, and further investigate its underlying effect on regulating NSCLC cell functions. Methods: 319 NSCLC patients who underwent resection were consecutively reviewed, and AKIP1 expression (in 319 tumor tissues and 145 adjacent tissues) was determined by immunohistochemistry. Disease‐free survival (DFS) and overall survival (OS) were calculated. In vitro, control overexpression, AKIP1 overexpression, control shRNA and AKIP1 shRNA plasmids were transfected into A549 cells to evaluate the effect of AKIP1 on cell proliferation and apoptosis. Results: A‐kinase‐interacting protein 1 expression was increased in tumor tissues compared to adjacent tissues, and it positively correlated with tumor size, lymph node metastasis and TNM stage in NSCLC patients. Kaplan‐Meier curves displayed that AKIP1 high expression correlated with worse DFS and OS, and multivariate Cox's regression revealed that it was an independent predictive factor for poor survival profiles. In vitro experiments displayed that AKIP1 expression was elevated in PC9 and A549 cells compared to normal lung epithelial cells; moreover, cell proliferation was increased by AKIP1 upregulation but reduced by AKIP1 downregulation, and cell apoptosis was decreased by AKIP1 upregulation but increased by AKIP downregulation in A549 cells. Interestingly, AKIP1 promoted fibronectin and zinc finger E‐box binding homeobox 1 expressions while reduced E‐cadherin expression in A549 cells. Conclusion: A‐kinase‐interacting protein 1 overexpression correlates with deteriorative tumor features and worse survival profiles and promotes cell proliferation but represses apoptosis in NSCLC.